ALGORITMA APRIORI MENENTUKAN BEST SELLER DURIAN DI KOTA BATAM - Koko Handoko; Pastima Simanjuntak; Erlin Elisa (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
The city of Batam is a city where immigrants are generally not native, day and night along the streets there are many people selling culinary delights, currently one of the things that is in great demand is durian which has many types such as durian in Bintan, Tanjung Batu, Medan, Padang, Palembang and Malaysia. The people of Batam, like those in general who live in Nongsa, Botania, Batam Center, Batu Aji, Tiban and Bengkong, buy durian from areas such as durian from Sumatra Island because there are many durian sellers on the side of the road day or night, but durian sellers in the Nagoya area generally sell durian from the Bintan, Ujung Batu and Malaysia areas with different prices from durian from Sumatra Island. With this, the author looks for manual results first and will match these results using the a priori algorithm method and assisted by RapidMiner software to ensure that the manual calculations carried out will get the same results using this software. The results of the calculations show that Musangking, Kampung, and 101 durian are the 3 types of durian that are very popular and liked by buyers at KimHui Batam Durian Shop.